2012
DOI: 10.1002/etc.2048
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the herbicide imazapyr on juvenile Oregon spotted frogs

Abstract: Abstract-Conflict between native amphibians and aquatic weed management in the Pacific Northwest is rarely recognized because most native stillwater-breeding amphibian species move upland during summer, when herbicide application to control weeds in aquatic habitats typically occurs. However, aquatic weed management may pose a risk for aquatic species present in wetlands through the summer, such as the Oregon spotted frog (OSF, Rana pretiosa), a state endangered species in Washington. Acute toxicity of herbici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…As in our previous study with juvenile Oregon spotted frogs [29], cricket consumption varied by day, although little difference was readily apparent between treatments (Figure 4). However, potential interactions among treatments and deformities were observed when graphs of cricket consumption data were examined (Supplemental Data, Figure S1), and data from our previous study indicated that sex may be important in cricket consumption patterns of juvenile ranid frogs [29]. We included sex and the presence/absence of limb deformities and scoliosis as random factors in the LMM for model exploration.…”
Section: Cricket Consumptionsupporting
confidence: 65%
See 1 more Smart Citation
“…As in our previous study with juvenile Oregon spotted frogs [29], cricket consumption varied by day, although little difference was readily apparent between treatments (Figure 4). However, potential interactions among treatments and deformities were observed when graphs of cricket consumption data were examined (Supplemental Data, Figure S1), and data from our previous study indicated that sex may be important in cricket consumption patterns of juvenile ranid frogs [29]. We included sex and the presence/absence of limb deformities and scoliosis as random factors in the LMM for model exploration.…”
Section: Cricket Consumptionsupporting
confidence: 65%
“…Weights (to 0.01 g) were collected at the start and end of the 96‐h exposure, at completion of metamorphosis, at 45 d post metamorphosis, and at the end of the 2‐mo grow‐out, when frogs were euthanized for liver collection. Mass and SVL were converted to body condition for analyses .…”
Section: Methodsmentioning
confidence: 99%
“…Historically, herpetologists have determined body condition in amphibians using body condition indices based on morphometric measurements, typically snout‐vent length, and bodyweight (Băncilă, Hartel, Plăiaşu, Smets, & Cogălniceanu, ; Bell, Carver, Mitchell, & Pledger, ; Denoël, Hervant, Schabetsberger, & Joly, ; Gendron et al, ; Leary, Jessop, Garcia, & Knappa, ; MacCraken & Stebbings, 2012; Pope & Matthews, ; Yahnke, Grue, Hayes, & Troiano, ). Fulton's index (based on the formula: k=ML3 where k = Fulton's factor, M = body mass, and L = length) has been used in leopard frogs ( Rana pipiens ) to assess the effect of an agricultural pesticide on lungworm infection (Gendron et al, ; Peig & Green, ).…”
Section: Discussionmentioning
confidence: 99%
“…BCS) was developed for the mountain chicken frog (Leptodactylus fallax) and assessed for intra-and inter-observer variability, as well as correlation with an objective measure of body condition (scaled mass index), in February and March 2016 just prior to the beginning of the breeding season. To the author's knowledge this is the first BCS to be developed and assessed for any amphibian species.Historically, herpetologists have determined body condition in amphibians using body condition indices based on morphometric measurements, typically snout-vent length, and bodyweight(Băncilă, Hartel, Plăiaşu, Smets, & Cogălniceanu, 2010;Bell, Carver, Mitchell, & Pledger, 2004;Denoël, Hervant, Schabetsberger, & Joly, 2002;Gendron et al, 2003;Leary, Jessop, Garcia, & Knappa, 2004; MacCraken & Stebbings, 2012;Pope & Matthews, 2002;Yahnke, Grue, Hayes, & Troiano, 2012). Fulton's index (based on the formula:k ¼ M L 3 where k = Fulton's factor, M= body mass, and L = length) has been used in leopard frogs (Rana pipiens) to assess the effect of an agricultural pesticide on lungworm infection (Gendron et al, 2003; Peig & Green, 2010).…”
mentioning
confidence: 99%
“…Parrotfeather in these sites was treated with an application of imazapyr in late summer of 2013 (1 month after the first survey). Imazapyr degrades quickly in water and is considered largely non‐toxic to aquatic organisms (Stehr et al ., ; Yahnke et al ., ). Based on univariate and multivariate comparisons between sampling years, we found no evidence for declines in fish density or differential shifts in fish communities between sites that were treated and those that were not.…”
Section: Methodsmentioning
confidence: 97%